Pengabulan Izin Poligami Dengan Alasan Sudah Terlanjur Nikah Siri - Asalia Lubian; Prahasti Suyaman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is entitled Granting Polygamy Permits on the Reason of Already Married Siri (Analysis of Judgment of the Sukabumi Religious Court Number 673/Pdt.G/2021/PA.Smi). This research will discuss how the panel of judges considers the granting of polygamy permits that do not meet the alternative requirements in the case decision number 673/Pdt.G/2021/PA.Smi, and what are the legal consequences of granting a polygamy permit in case decision number 673/Pdt.G /2021/PA. Smi. The results of the analysis regarding the consideration of the panel of judges regarding the consideration of the panel of judges regarding the granting of permission for polygamy that does not meet alternative requirements in the decision on case number 673/Pdt.G/2021/Pa.Smi can be understood that the consideration of the panel of judges for the decision in case number 673/Pdt. G/2021/Pa.Smi refers to legal considerations namely, Article 4 paragraph (2) letter (a), Article 5 paragraph (1) letter (a) and paragraph (2) of Law Number 1 of 1974 jo article 41 letter (b) Government Regulation Number 9 of 1975 in conjunction with article 57 letter (a) and article 58 paragraph (1) letter (a), paragraph (2) and paragraph (3) of the Compilation of Islamic Law. As well as evidence in the form of P.1-P.12, and the testimony of the two witnesses who were questioned during the trial process. The granting of a permit for polygamy in case decision Number 673/Pdt.G/2021/Pa.Smi has significant implications in a legal and social context.